Simultaneous fabrication of line and dot dual nanopatterns using miktoarm block copolymer with photocleavable linker - Chungryong Choi (Nature Portfolio, 2017)
Block copolymers that form nanodomains and are used in nanolithography usually do not form nanopatterns with multiple shapes. Here the authors report a block copolymer that allows for UV- induced cleavage of one arm and demonstrate the transformation of the cylindrical to the lamellar nanodomain.